Flood analysis of December 2006: focus at Segamat Town, Johor - Muhammad Barzani Gasim; Salmijah Surif; Mazlin Mokhtar, Mohd. Ekhwan; Hj. Toriman, Sahibin Abd. Rahim; Chong, Huei Bee (Universiti Kebangsaan Malaysia, 2010)
This study aimed to ascertain the causes of Segamat flood which occurred from 17 to 21 December 2006. Actvities include collection, evaluation and analysis of rainfall data from January 1998 to December 2006, and analysis of daily telemetry for water levels and discharge in December 2006. The daily, monthly and annual rainfall of Felda Medoi Station, Segamat were analyzed and correlated with the telemetry data. Based on the 9 years rainfall data, monthly rainfall in Segamat area ranged from 2.5 mm (Februari 2004) to 536.8 mm (January 2003). Monthly rainfall distribution from October to December 2006 increased from 118 mm to 435 mm but decreased (392 mm) in January 2007. Our result showed that extra ordinary heavy downpour, low and undulating topography of the study area was identified as the main cause for the Segamat flood. Keywords: 2006 Segamat flood; Felda Medoi station; stream flow; telemetry data